Innovations in land tenure reform and administration in Africa - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Land and the institutions that govern its ownership and use greatly affect economic growth and poverty reduction. Lack of access to land and inefficient or corrupt systems of land administration have a negative impact on a country's investment climate. Well-functioning land institutions and markets improve it, reducing the cost of accessing credit for entrepreneurs and contributing to the development of financial systems. Access to even small plots of land to grow crops can also greatly improve food security and quality. Broad-based land access can provide a basic social safety net at a cost far below alternative government programs, allowing governments to spend scarce resources on productive infrastructure. Policies that foster lease markets for land can also contribute to the emergence of a vibrant nonfarm economy.